Finding the Right Shade of Green: The Effect of Advertising Appeal Type on Environmentally Friendly Consumption - Green, Todd; Peloza, John (Journal of advertising, 2014)
There are two forms of advertising appeals for environmentally friendly products and policies: those that provide consumer benefit (e.g., cost savings) and those that provide societal benefit (e.g., lower emissions). This research examines the role of decision-making and consumption contexts on the efficacy of each appeal. The results of three studies indicate that in contexts where consumers experience heightened public accountability they are more responsive to other-benefit appeals, and in more private settings they favor self-benefit appeals. We replicate this finding across multiple samples, product categories, and consumption and decision-making contexts. Our findings reconcile previously conflicting research on the efficacy of either appeal type and provide guidance for marketers seeking to promote environmentally friendly consumption.